The art of inhabiting as a technique for subjectification - Assennato, Marco (Itinerari, 2024)
The aim of the article is a radical rethinking of the relationship between architecture and dwelling, starting with a critique of the famous lecture Martin Heidegger gave in Darmstadt in 1956. In the foreground comes the question – central to architecture – of the technical modification of the environment and thus of our ability to inhabit the planet.